Paciente adolescente de 16 años con epilepsia - Landivar Ayala, Joyce María (2019)
In the clinical case presented below, the case of a female adolescent patient of 16 years who was taken by her mother to the emergency room due to convulsions accompanied by fever and loss of consciousness, the mother of the patient reports that The adolescent has presented seizures since she was 12 years old but has not followed a constant treatment. Taking into account the condition of the patient and the history of seizures, the doctor orders an encephalogram and a complete blood test to make a diagnosis and therefore a treatment. In the first place, the nurse assesses the physical state of the patient in order to issue a differential diagnosis, in this case there is a risk of aspiration R / C decrease in the level of consciousness, so she elaborates a nursing care plan based on the diagnosis of the patient. patient to prevent complications and once stabilized and treated by the doctor to follow up on the evolution of the case. It is important to keep in mind that epileptic seizures often occur without symptoms or apparent triggers, so you should be aware if a person has already presented more than 3 three seizure symptoms, see a specialist who can make a diagnosis and prescribe a treatment so that stronger seizures that compromise the integrity of the person can be prevented